AdaptiveGCN: Efficient GCN Through Adaptively Sparsifying Graphs - Li, Dongyue; Yang, Tao; Du, Lun; He, Zhezhi; Jiang, Li (ACM International Conference on Information & Knowledge Management (CIKM'21), 2021)
Graph Convolutional Networks (GCNs) have become the prevailing approach to efficiently learn representations from graph-structured data. Current GCN models adopt a neighborhood aggregation mechanism based on two primary operations, aggregation and combination. The workload of these two processes is determined by the input graph structure, making the graph input the bottleneck of processing GCN. Meanwhile, a large amount of task-irrelevant information in the graphs would hurt the model generalization performance. This brings the opportunity of studying how to remove the redundancy in the graphs. In this paper, we aim to accelerate GCN models by removing the task-irrelevant edges in the graph. We present AdaptiveGCN, an efficient and supervised graph sparsification framework. AdaptiveGCN adopts an edge predictor module to get edge selection strategies by learning the downstream task feedback signals for each GCN layer separately and adaptively in the training stage, then only inference with the selected edges in the test stage to speed up the GCN computation. The experimental results indicate that AdaptiveGCN could yield 43% (on CPU) and 39% (on GPU) GCN model speed-up averagely with comparable model performance on public graph learning benchmarks.